Perbedaan Pola Asuh Anak dari Keluarga yang Menikah di Usia Muda dengan Usia Ideal di Desa Bukit Bungkul Kecamatan Renah Pamenang Kabupaten Merangin - Listianie, Yully (Jurnal Siber Multi Disiplin, 2023)
This study aims to describe the upbringing of children from families who married at a young age with the ideal age and to find out the differences in parenting styles for families who married at a young age and the ideal age in Bukit Bungkul Village, Renah Pamenang District, Merangin Regency. This research is quantitative. The population in this study were 15 mothers who married at a young age and 15 mothers who married at the ideal age. The sample is the entire population that is used as a respondent. The technique used is a questionnaire. The tool used is a list of questions. Data analysis using the percentage formula and t-test. After analyzing the data obtained from the research findings, it can be concluded that there is no difference in the parenting style of children from families who marry at a young age and the parenting styles of children from families who marry at a young age.